Criação de ilustrações baseadas em modelos de composição de jogos de cartas colecionáveis para o jogo eletrônico Hearthstone - Freitas, Caio Ramon Gomes de (2022)
The general objective of this final paper is to describe, in the form of a technical report, the development of digital illustrations following the visual style of the game Hearthstone using character and scenery design methodologies present in collectible card games. The process not only involves listing and investigating all the visual aspects of the game in question, but also seeks to investigate the composition and construction motives that permeate the creation of collectible card game art as a whole in a fundamental way. The case study addresses areas of interest that are helpful in creating visual illustrations for the virtual collectible card game Hearthstone, plot aspects, game rules, and reference suggestions. The product development was done as a way to apply the aforementioned case study and for this, creation methodologies based on design thinking were used that allow a systematic way of creating. It is then reported the development of the illustration from its abstract conception, which steps were part of the workflow, the results obtained and which areas can be expanded.